Clinical features, biochemistry, and HLA‐DRB1 status in youth‐onset type 1 diabetes in Mali. Issue 8 (10th September 2022) - Besançon, Stéphane; Govender, Denira; Sidibé, Assa Traore; Noble, Janelle Annette; Togo, Amagara; Lane, Julie Ann; Mack, Steven John; Atkinson, Mark A.; Wasserfall, Clive Henry; Kakkat, Faizy; Martin, Gregory G. N.; Ogle, Graham David
Abstract: Objective: Limited information is available regarding youth‐onset diabetes in Mali. We investigated demographic, clinical, biochemical, and genetic features in new diabetes cases in children and adolescents. Research Design and Methods: The study was conducted at Hôpital du Mali in Bamako. A total of 132 recently‐diagnosed cases <21 years were enrolled. Demographic characteristics, clinical information, biochemical parameters (blood glucose, HbA1c, C‐peptide, glutamic acid decarboxylase‐65 (GAD‐65) and islet antigen‐2 (IA2) autoantibodies) were assessed. DNA was genotyped for HLA‐DRB1 using high‐resolution genotyping technology. Results: A total of 130 cases were clinically diagnosed as type 1 diabetes (T1D), one with type 2 diabetes (T2D), and one with secondary diabetes. A total of 66 (50.8%) T1D cases were males and 64 (49.2%) females, with a mean age at diagnosis of 13.8 ± 4.4 years (range 0.8–20.7 years) peak onset of 15 years. 58 (44.6%) presented in diabetic ketoacidosis; with 28 (21.5%) IA2 positive, 76 (58.5%) GAD‐65 positive, and 15 (11.5%) positive for both autoantibodies. HLA was also genotyped in 195 controls without diabetes. HLA‐DRB1 genotyping of controls and 98 T1D cases revealed that DRB1*03:01, DRB1*04:05, and DRB1*09:01 alleles were predisposing for T1D (odds ratios [ORs]: 2.82, 14.76, and 3.48, p ‐values: 9.68E‐5, 2.26E‐10, and 8.36E‐4, respectively), while DRB1*15:03 was protective (OR = 0.27; p ‐value = 1.73E‐3). No significant differences were observed between T1D cases with and without GAD‐65 and IA2 autoantibodies. Interestingly, mean C‐peptide was 3.6 ± 2.7 ng/ml (1.2 ± 0.9 nmol/L) in T1D cases at diagnosis. Conclusions: C‐peptide values were higher than expected in those diagnosed as T1D and autoantibody rates lower than in European populations. It is quite possible that some cases have an atypical form of T1D, ketosis‐prone T2D, or youth‐onset T2D. This study will help guide assessment and individual management of Malian diabetes cases, potentially enabling healthier outcomes.